Optimasi Volume Kit Da An Gene Untuk Deteksi SARS-CoV-2 dengan Real Time RT-PCR - Seprianto Seprianto; Muhammad Arreza; Titta Novianti; Febriana Dwi Wahyuni; Oktaviani Naulita Turnip; Roaslein Putri; Henny Saraswati (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: SARS-CoV-2 is a new type of coronavirus of the genus Betacoronavirus and the family Coronaviridae that causes a respiratory disease called COVID-19. The virus has a sheath and genetic material in the form of single-chain RNA. The genome structure of this virus is divided into two types, namely genes that encode non-structural proteins consisting of the ORF1a / ORF1b gene and genes that encode structural proteins consisting of spike glycoprotein (S), envelope (E), membrane glycoprotein (M), and nucleocapsid protein (N). Methods: The method of detecting SARS-CoV-2 with real time RT-PCR is the most recommended method because it has high specificity and accuracy. The specificity of a method is necessary to be able to specifically recognize the pathogen that causes the disease. Real time RT-PCR requires sampling with a swab on the oropharynx or nasopharynx to be examined in the laboratory which later the presence of viral RNA becomes a molecule that is assessed for diagnosis results. In this study, volume optimization was carried out on the Da An Gene kit used for the detection of SARS-CoV-2 with Reverse Transcription Polymerase Chain Reaction (Real time RT-PCR) with the aim of saving the use of reagents from available kits but with amplification results remaining optimal and accurate. Results: There were three SARS-CoV-2 RNA samples used consisting of N62, N63, and N79 samples and three types of total volume used were 20 Î¼l, 15 Î¼l, and 10 Î¼l. The results of this study showed that the three positive samples contained SARS-CoV-2 with a Cq value of < 40. Conclusion: A volume of 20 Î¼l is the optimal volume, which is more efficient than the manufacturer's recommended volume of 25 ul.